UV photodissociation and population dynamics of some important Criegee intermediates - Nikoobakht, Behnam; Menger, Maximilian; Köppel, Horst (Physical chemistry, chemical physics, 2025)
The influence of Criegee intermediates [CH2OO, (CH3)2COO, syn- and anti-CH3CH2CHOO] on atmospheric chemistry depends significantly on their photodissociation dynamics under irradiation by sunlight. In this review, we highlight examples of electronic structure (multireference electronic wave functions) and nuclear quantum dynamics calculations relying on the wavepacket propagation technique for studying photodissociation dynamics of the Criegee intermediates in the visible or near UV region. In general, two interacting electronic states and three nuclear degrees of freedom are considered for construction of model Hamiltonians in our investigation. The UV absorption spectra are found to agree very well with available experimental recordings when accounting for broadening effects due to vibrational and rotational congestion and lifetime effects. This result serves to validate the Hamiltonian model built within the quasi-diabatic representation. It is found that the vibronic coupling is a vital ingredient to provide accurate insight into the photodissociation of these atmospheric species along the O-O bond and for reproducing the experimental absorption spectra, especially for the larger species (CH3)2COO, syn- and anti-CH3CH2CHOO. Time-dependent electronic populations reveal a faster decay than for the smaller system CH2OO. This is interpreted in terms of the stronger coupling between the B and C states in the larger systems (CH3)2COO, syn- and anti-CH3CH2CHOO leading to the shorter lifetime for the B state compared to CH2OO.
Gesehen am 21.01.2026